SOSIALISASI ANALISIS PENYEBAB BENCANA LONGSOR DESA SIRAU, KARANGMONCOL, PURBALINGGA - Sachrul Iswahyudi; Asmoro Widagdo; FX Anjar Tri Laksono (DHARMA BAKTI, 2021)
In the rainy season, land movement disasters are common in vulnerable areas. InNovember 2020, there was a landslide disaster in Sirau Village, Purbalingga. Thisphenomenon needs to be continuously informed to the public parties in order to minimizethe risks and losses as little as possible. This community service activity aims to providesocialization and understanding to government officials and the community about landslidesat the location. These activities are using methods of literature study, field surveys and directdiscussion in the field. The landslide disaster in Sirau Village is interpreted as being causedby several factors, including: morphology, lithology, geological structure, weathering,rainfall, and land use